2021
DOI: 10.1186/s13031-021-00412-2
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of health systems in conflict affected governorates of Iraq, 2014–2018

Abstract: Objectives The objective of this study was to assess the resilience of health systems in four governorates affected by conflict from 2014 to 2018, and to convey recommendations. Methods Health managers from Al Anbar, Ninawa, Salah al-Din, and Kirkuk governorates discussed resilience factors of Primary Health Care services affected by the 2014–2017 ISIS insurgency in focus groups, and general discussions. Additional information was gathered from ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 15 publications
(18 reference statements)
0
38
0
Order By: Relevance
“…ISIS signifi cantly infl uenced a health system that had already been damaged by years of strife and underfunding. Despite the fact that ISIS had been operating in several areas for some time, many health facilities had little notice of the imminent attack (Ibrahim et al,2021). Most cases were detected in female individuals compared to males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISIS signifi cantly infl uenced a health system that had already been damaged by years of strife and underfunding. Despite the fact that ISIS had been operating in several areas for some time, many health facilities had little notice of the imminent attack (Ibrahim et al,2021). Most cases were detected in female individuals compared to males.…”
Section: Discussionmentioning
confidence: 99%
“…ISIS directly affected the health system. This could cause the spread of some diseases, especially parasitic diseases ( Ibrahim et al, 2021 ). Many studies have documented the epidemiology of E. vermicularis in Iraqi populations from various regions.…”
Section: Introductionmentioning
confidence: 99%
“…Iraq, Afghanistan, and Nigeria), healthcare systems face significant setbacks due to reduced tax revenues, increased healthcare costs to provide emergency care coverage, and decreased funding from international aid agencies and other donor organizations due to security concerns and a perceived lack of stability in the affected region. [20][21][22][23] Some reports have also demonstrated that healthcare workers are unpaid where services are chronically underfunded, leaving no medicofinancial exponentiation to facilitate productivity. 20,22 These issues highlight how it is arduous to procure basic healthcare services for those in need, exacerbating the already dire consequences of terrorism.…”
Section: Worsening Financial Shortages In Lmic Healthcare Systemsmentioning
confidence: 99%
“…21 22 Other research in deteriorated security context has primarily focused on the attacks on health systems, 23 24 and the experience 25 and coping strategies deployed by health professionals. [26][27][28][29][30][31][32] Maternal and child health have been extensively studied. [33][34][35] Studies in Yemen and Syria, in particular, offer a stimulating comparative perspective as they relate to high-intensity conflicts involving considerable means of destruction and weaponisation of healthcare (ie, the use of the destruction of the health system as a component of the military strategy 31 ) unknown in Mali at the time of this study.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…30 In Iraq, a study also points out that the adaptability of health centres is very limited, especially when they are cut-off from the support of the Ministry of Health or supplies. 32 However, the comparison with Syria suggests that the health system had more resources at the beginning of the conflict, which enabled it to develop more ambitious adaptation strategies despite a conflict of higher intensity. 27 Typology of resilience process components A limit to the concept of health system resilience seems to be semantic.…”
Section: Bmj Global Healthmentioning
confidence: 99%